The spread of COVID-19 and attending football matches: Lesson from Belarus - Parshakov, P. (SSRN, 2021)
The COVID-19 pandemic shut down sporting events. However, the Belarusian Premier League was the only top-flight European league not suspended during COVID-19 pandemics. In this study, we analyze the effect of attending football matches on the number of COVID-19 cases. The results show, that 1% growth in match attendance in a region increases the number of COVID-19 cases by 0.15%-0.48% percent. This evidence might be interesting for sports leagues that develop their reopening policies.